2016
DOI: 10.1377/hlthaff.2016.0829
|View full text |Cite|
|
Sign up to set email alerts
|

Dental Care And Medicare Beneficiaries: Access Gaps, Cost Burdens, And Policy Options

Abstract: Despite the wealth of evidence that oral health is related to physical health, Medicare explicitly excludes dental care from coverage, leaving beneficiaries at risk for tooth decay and periodontal disease and exposed to high out-of-pocket spending. To profile these risks, we examined access to dental care across income groups and types of insurance coverage in 2012. High-income beneficiaries were almost three times as likely to have received dental care in the previous twelve months, compared to low-income ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 10 publications
(17 reference statements)
1
45
2
Order By: Relevance
“…Our findings did not identify income as a predictor of having a dentist, a finding that differs from some other studies . In a recent report using data from the Medicare Current Beneficiary Survey, high‐income Medicare beneficiaries were three times as likely to have received dental care in the previous year than low‐income beneficiaries .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings did not identify income as a predictor of having a dentist, a finding that differs from some other studies . In a recent report using data from the Medicare Current Beneficiary Survey, high‐income Medicare beneficiaries were three times as likely to have received dental care in the previous year than low‐income beneficiaries .…”
Section: Discussioncontrasting
confidence: 99%
“…Needing help with transportation was another predictor identified in our study, and transportation issues have also been cited as a significant barrier for older adults in accessing dental care . We also observed that having dental insurance was a strong predictor of having a dentist, and the way insurance coverage impacts access to dental care has been reported for the US older adult population and seems to be a worldwide trend …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Studies that have examined dental insurance coverage among adults in the United States have provided evidence to support the provision of increased dental coverage to improve overall health of older adults (Kreider, Manski, Moeller, & Pepper, 2015;Willink et al, 2016). The aim of the present study was to examine the relationship between dental coverage and self-reported health over time in a national sample of older Americans.…”
Section: Introductionmentioning
confidence: 95%
“…Dental coverage for the elderly population in the United States is limited, with only 12% of adults aged 65 years and older having such coverage (Willink, Schoen, & Davis, 2016). The elderly have limited options for dental coverage, as the largest health insurance provider for adults 65 and older, Medicare, does not cover dental care unless it coincides with medical needs (US Centers for Medicare and Medicaid Services, 2017).…”
Section: Introductionmentioning
confidence: 99%